2017
DOI: 10.3389/fpsyg.2017.00258
|View full text |Cite
|
Sign up to set email alerts
|

Contentment Duration Mediates the Associations between Anxious Attachment Style and Psychological Distress

Abstract: Relatively little is known about the emotional processes underlying the association between adult attachment styles and psychological distress. This study aims to examine the role of contentment in terms of intensity and duration in the positive associations between anxious and avoidant attachment styles and psychological distress. A sample of 284 Chinese university students completed a self-reported questionnaire on attachment styles, intensity and duration of contentment, and anxiety and depressive symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…For example, many studies have found that attachment anxiety is highly correlated with generalized anxiety (e.g., rs ≥ .47; Bekker & Croon, 2010;English et al, 2018;O'Neill & Murray, 2016). In contrast, other studies have reported a more moderate correlation between attachment anxiety and generalized anxiety (e.g., r ≤ .24; Kidd et al, 2016;Meredith et al, 2016;Ng & Hou, 2017;Patel, 2008). Similarly, one large-scale study found a very large correlation between attachment avoidance and depression (e.g., r ≥ .47; Gallagher et al, 2017;Joeng et al, 2017;Pandeya, 2017), whereas other studies have reported a moderate correlation between these variables (e.g., r ≤ .20; Bekker & Croon, 2010;Gnilka et al, 2013;Necef, 2014;Ng & Hou, 2017;Rholes et al, 2011).…”
Section: Adult Attachment and Mental Healthmentioning
confidence: 99%
“…For example, many studies have found that attachment anxiety is highly correlated with generalized anxiety (e.g., rs ≥ .47; Bekker & Croon, 2010;English et al, 2018;O'Neill & Murray, 2016). In contrast, other studies have reported a more moderate correlation between attachment anxiety and generalized anxiety (e.g., r ≤ .24; Kidd et al, 2016;Meredith et al, 2016;Ng & Hou, 2017;Patel, 2008). Similarly, one large-scale study found a very large correlation between attachment avoidance and depression (e.g., r ≥ .47; Gallagher et al, 2017;Joeng et al, 2017;Pandeya, 2017), whereas other studies have reported a moderate correlation between these variables (e.g., r ≤ .20; Bekker & Croon, 2010;Gnilka et al, 2013;Necef, 2014;Ng & Hou, 2017;Rholes et al, 2011).…”
Section: Adult Attachment and Mental Healthmentioning
confidence: 99%
“…Positive emotions could become bipolar to negative emotions and have the power of undoing negative psychological impact of stressful situations (Hou et al, 2015; Tugade & Fredrickson, 2004; Zautra, Smith, Affleck, & Tennen, 2001). More anxious attachment was found to contribute to shorter duration of contentment in daily events, which in turn was associated with higher psychiatric symptoms (Ng & Hou, 2017). The counterregulation perspective further implicates the human tendency to attend to context-incongruent information across situations depending on activated motivational and/or emotional states (Rothermund, Voss, & Wentura, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In humans though the costs of emotions, like the one from the urge of want, and their cognitive costs can become predominant. Thus, besides some focus on duration [127,128], mainly the cost of suppressing emotions is monitored [129]. Fortunately affect dynamics are taking momen-tum also in the case of a likely alias of increased emotional effort suspected to be a pre-depressive signature of decoup-ling from usual functional connectivity: rigid emotional inertia [130]…”
Section: Effortful Controls Of Thought Action Moodmentioning
confidence: 99%